The Persistence and Change in China’s Healthcare Insurance Reform: Clues from Fiscal Subsidy Policies Made for Settling COVID-19 Patients’ Medical Costs - Ma T; Guo B; Xu J (Dove Medical Press, 2022)
Teng Ma,1 Bao Guo,2 Ju Xu3 1Law School & Intellectual Property School, Jinan University, Guangzhou, 510632, People's Republic of China; 2School of Law, Xiamen University, Xiamen, 361005, People's Republic of China; 3Library, Longyan University, Longyan, 364012, People's Republic of ChinaCorrespondence: Ju Xu, Library, Longyan University, 1# Dongxiaobei Road, Longyan, 364012, People's Republic of China, Tel +86 18613048699, Email josephine.xu@foxmail.comBackground: The system studied in this article is set in the development and reform of China's healthcare insurance, the time mentioned in this article is during the COVID-19 period and the issues are about healthcare insurance fiscal subsidy policies for COVID-19 patients' medical costs.Methods: Method of comparison and method of case study are used. This article compares the healthcare insurance systems, fiscal subsidy policies during the COVID-19 period and takes Yulin's healthcare insurance reform and Nanjing healthcare insurance administration's measures to fight against COVID-19 pandemic as specific cases to analyze.Aim: This article presents the advantages of the coverage of China's healthcare insurance as well as the insufficiency of the commercial healthcare insurance and market-oriented medical institutions to show the persistence and change in China's healthcare insurance reform.Conclusion: Soon after the outbreak of COVID-19 pandemic, the National Healthcare Security Administration and the Ministry of Finance of PRC jointly issued an announcement on how to guarantee the medical security of the novel coronavirus pneumonia pandemic. More specific policies were made by each province to secure that the total medical costs of the COVID-19 confirmed and suspected patients were almost borne by healthcare insurance and government finance subsidy. These policies reveal two basic points ahead China's healthcare reform: one is that China shall persist in positively promoting the universal healthcare insurance coverage program, which will break down barriers between urban and rural areas; the other is that the commercial medical insurance shall be a supplementary to social healthcare insurance and the market-oriented medical institutions shall be encouraged. The two basic points stand for the persistence and change in China's healthcare reform. China's healthcare insurance reform should accord with the requirement in specific age and stage.Keywords: healthcare insurance, COVID-19 pandemic, medical costs, public health, disease prevention